Clinical Utility of Cytomegalovirus Viral Load in Bronchoalveolar Lavage in Lung Transplant Recipients - Chemaly, Roy F.; Yen‐Lieberman, Belinda; Chapman, Jeffrey; Reilly, Amy; Bekele, B. Nebiyou; Gordon, Steven M.; Procop, Gary W.; Shrestha, Nabin; Isada, Carlos M.; DeCamp, Malcolm; Avery, Robin K. (American journal of transplantation, 2005)
The utility of cytomegalovirus (CMV) viral load (VL) by quantitative hybrid capture assay (Q‐HCA) was investigated in bronchoalveolar lavage (BAL) from lung transplant recipients and compared with BAL cultures and blood VL. Forty‐three consecutive BAL samples from 27 lung transplant recipients were analyzed. All samples had shell vial (SV) cultures in addition to Q‐HCA. Histopathology was done on all lung tissues, and immunohistochemistry (IHC) in those with positive CMV cultures. Fifteen (56%) lung transplant recipients had both positive BAL SV cultures and BAL VL. Five of 15 had CMV pneumonitis with a VL in BAL >500 000 copies/mL (mean: 1638 450). Ten patients without CMV pneumonitis had VL in BAL <500 000 copies/mL (mean 81 820, p = 0.002). High VL in BAL and blood invariably meant CMV pneumonitis, but 2 patients with CMV pneumonitis had high BAL VL but relatively low blood VL. Initial CMV seronegativity was associated with pneumonitis (4/5 vs. 1/10; p = 0.004) and higher BAL CMV VL (p = 0.03). High CMV BAL or blood VL did not correlate with acute rejection or development of bronchiolitis obliterans syndrome (BOS). High CMV VL in BAL in lung transplant recipients is strongly associated with CMV pneumonitis, and may be more predictive than peripheral blood viral load.